2017
DOI: 10.21470/1678-9741-2017-0085
|View full text |Cite
|
Sign up to set email alerts
|

The Left Atrial Appendage Revised

Abstract: Nonvalvular atrial fibrillation is associated with a 4- to 5-fold strokes increase and may be responsible for 15% to 20% of all strokes in the elderly. In this scenario, the left atrial appendage thrombus would be the associated with 90% of cases. The use of anticoagulants, percutaneous devices, and the left atrial appendage surgical exclusion is still an open discussion. For left atrial appendage procedures, relevant anatomic spatial relationships have to be emphasized, besides the chance of the normal physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…A series of studies have demonstrated that prolonged AF results in the loss of effective atrial contraction and atrioventricular synchrony. 2 , 6 , 7 , 21 23) In this prospective, self-controlled study, we evaluated left atrial volume and left atrial hemodynamic performance by real-time three-dimensional echocardiography. The LA size at baseline was obviously beyond the cutoff of 35 mm for the enrolled AF patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of studies have demonstrated that prolonged AF results in the loss of effective atrial contraction and atrioventricular synchrony. 2 , 6 , 7 , 21 23) In this prospective, self-controlled study, we evaluated left atrial volume and left atrial hemodynamic performance by real-time three-dimensional echocardiography. The LA size at baseline was obviously beyond the cutoff of 35 mm for the enrolled AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have shown that the LAA is largely involved in ANP secretion and plays an important role in body fluid modulation. 7 , 11) In a clinical study, Yoshihara et al 27) demonstrated that ANP secretion was attenuated in the early postoperative period after the Maze procedure, including bilateral atrial appendectomy, and it persisted in the chronic phrase. Concurrently, this attenuated ANP directly affects body fluid balance during the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, o apêndice possui a maior concentração de grânulos de peptídeo natriurético atrial (PNA) do AE 22 (cerca de 30%). 4,23 O estímulo para secreção de PNA é a distensão dos cardiomiócitos, e, por ser mais complacente e concentrar a maior quantidade de PNA, o AAE é mais sensível às variações de volume e pressão e exerce maior controle sobre a redução da pressão arterial e aumento da frequência cardíaca, diurese e natriurese. 4,23,24 O AAE realiza contração ativa, 4 e sua velocidade de fluxo pode ser quantificada pelo Doppler pulsátil.…”
Section: Função Do Apêndice Atrial Esquerdounclassified
“…4,23 O estímulo para secreção de PNA é a distensão dos cardiomiócitos, e, por ser mais complacente e concentrar a maior quantidade de PNA, o AAE é mais sensível às variações de volume e pressão e exerce maior controle sobre a redução da pressão arterial e aumento da frequência cardíaca, diurese e natriurese. 4,23,24 O AAE realiza contração ativa, 4 e sua velocidade de fluxo pode ser quantificada pelo Doppler pulsátil. Na maioria dos pacientes submetidos ao ecocardiograma transesofágico (ECO-TE), esse fluxo é quadrifásico 4,25,26 (Figura 2).…”
Section: Função Do Apêndice Atrial Esquerdounclassified